Condition assessment of civil infrastructure - Onoufriou, Toula; Casciati, Fabio (My University, 2015)
Ageing civil infrastructure systems together with the limited financial and depleting natural resources has become an important area of research that poses significant challenges to the research community and owners for maintaining or extending the life of existing infrastructures. Structural deterioration can significantly change the performance of the structure, and, therefore, monitoring actions, prediction techniques of its condition as well as retrofit techniques are important in maintaining its condition and safety at a desired level over time.
Keywords: Civil infrastructure systems; Wireless sensors; Communications; Bridge structures